1992
DOI: 10.1002/jnr.490310313
|View full text |Cite
|
Sign up to set email alerts
|

Focal, extracellular recording of slow miniature junctional potentials at the mouse neuromuscular junction

Abstract: Miniature endplate potentials (MEPPs) with slow rising phase can be attributed either to burst of transmitter releases or to distortion of conduction from remote releasing sites. The spontaneous activity of neuromuscular junctions recorded extracellularly at mouse diaphragms using sharp electrodes was analyzed to test these two hypotheses. The miniature junctional potentials (MEJPs) frequencies observed intracellularly as compared to MEPP frequency measured intracellularly in controls indicate that most events… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…While Katz's studies used muscle cells that were 30–50 micrometers in diameter, the muscle cells studied by Kriebel were only 6–10 micrometers in diameter. These findings were subsequently confirmed by others (Vautrin and Mambrini, 1981; Muniak et al, 1982; Wiegand et al, 1984; Erxleben and Kriebel 1988a, 1988b; Vautrin and Kriebel, 1991, 1992). Kriebel named each of the subunit signals of mEPPs as a subminiature end‐plate potentials (sub‐mEPP).…”
Section: Vesicle Diameter and Volumesupporting
confidence: 61%
“…While Katz's studies used muscle cells that were 30–50 micrometers in diameter, the muscle cells studied by Kriebel were only 6–10 micrometers in diameter. These findings were subsequently confirmed by others (Vautrin and Mambrini, 1981; Muniak et al, 1982; Wiegand et al, 1984; Erxleben and Kriebel 1988a, 1988b; Vautrin and Kriebel, 1991, 1992). Kriebel named each of the subunit signals of mEPPs as a subminiature end‐plate potentials (sub‐mEPP).…”
Section: Vesicle Diameter and Volumesupporting
confidence: 61%
“…It was shown that during development, hyperosmotic shock, or poisoning of the presynaptic terminal, miniature endplate potentials can show the same variability as miniature signals at central synapses, with a predominance of small amplitudes and short rise times. 18,20 Normal and small‐amplitude miniature endplate currents were shown to originate from the same release sites 33 and the release process to reversibly switch dynamically between the two types of mEPSPs. 21,20 One explanation for this phenomenon could be a change in the number and level of synchronization between TDs.…”
Section: Discussionmentioning
confidence: 99%
“…Long rise time events induced by acute treatments are not due to remote transmitter action for the following reasons: (1) long rise times may be recorded with focal extracellular electrodes (Cooke and Quastel, 1973;Augustine and Levitan, 1983;Vautrin and Kriebel, 1992); (2) plitude and rise time relationship of signals generated at remote sites would be negatively correlated, whereas the data showed a positive correlation (Fig. 2D; Erxleben and Kriebel, 1986b;Vautrin and Kriebel, 1991a); and (3) many signals with long rise times had breaks (Vautrin and Kriebel, 1992). Spontaneous events are known to clump (Cohen et al, 1973;Kriebel and Stolper, 1975;Vautrin and Kriebel, 1991).…”
Section: Analyses Of Mepcsmentioning
confidence: 99%